International patients in a Turkish hospital: a quantitative study on cross-border health care at the intersection of Eastern Europe, Asia and the Middle East - De Neve, Jan-Walter; Davé, Rahool; Gürel, Meltem; Subramanian, S. V. (World hospitals and health services, 2012)
This is the first attempt, to our knowledge, that aims to empirically quantify and characterize international patient flows to Turkey. A cross-sectional retrospective study was performed on consecutive patients seen at the International Services Department of a 209-bed private hospital in urban Turkey. Over six months, international patients represented 4 percent and 6 percent of all consultations and surgical procedures, respectively. Six hundred and fifty unique international patients received health care and represented 44 different countries. Among these 650 unique encounters, most patients originated from Bulgaria (37%), Romania (35%), Azerbaijan (6%), Iraq (3%) and Georgia (3%). International patients commonly required oncological (54%), surgical (13%) and neurological (7%) services. Although quantitative data on medical travel to Turkey is limited, significant patient flows exist from neighboring countries to Turkey.